Nearly a decade of groundbreaking speckle interferometry at the international Gemini observatory - Howell, Steve B.; Martínez-Vázquez, Clara E.; Furlan, Elise; Scott, Nicholas J.; Matson, Rachel A.; Littlefield, Colin; Clark, Catherine A.; Lester, Kathryn V.; Hartman, Zachary D.; Ciardi, David R.; Deveny, Sarah J. (Frontiers in Astronomy and Space Sciences, 2025)
Since its inception, speckle interferometry has revolutionized high-resolution astronomical imaging, overcoming atmospheric challenges to achieve the diffraction limits of telescopes. Almost a decade ago, in 2018, a pair of speckle cameras – ‘Alopeke and Zorro–were installed at two of the largest apertures in the world, the twin 8.1-m Gemini North and South telescopes in Hawai’i and Chile. Equipped with dual blue and red channels, ’Alopeke and Zorro deliver high-resolution imaging across the optical bandpass from 350 to 1,000 nm, which has led to crucial discoveries in both stellar multiplicity and exoplanetary science. Furthermore, the broad and nonrestrictive access to these instruments, given by each Gemini Observatory partner and via the US NOIRLab open skies policy, has allowed the community to expand the applications of the instruments, supporting a wide range of scientific investigations from Solar System bodies, to morphological studies of stellar remnants and quasars, to evolved stars, to transient phenomena. This paper reviews the instrument technology and observational capabilities, and highlights key scientific contributions and discoveries of ‘Alopeke and Zorro, emphasizing the enduring importance of speckle interferometry in advancing modern observational astronomy and expanding the frontiers of astronomical research.